An organic-inorganic hybrid battery separator, preparation method thereof and aqueous zinc ion battery

By using organic-inorganic hybrid battery separators prepared in combination with boron-containing inorganic particles and organic polymers, the problems of high cost of existing separators and unsuitable for aqueous zinc ion batteries are solved, and the electrochemical performance of the battery and the production cost are improved. effect.

CN118867575BActive Publication Date: 2025-02-14UNIV OF SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411312589.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-02-14
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The separator materials of existing water-based zinc ion batteries are costly and are not suitable for water-based zinc ion batteries. In addition, traditional surface functionalization methods cause dense coatings to clog the pores of the base membrane, affecting ion transport.

Method used

The organic-inorganic hybrid battery separator is prepared by composited boron-containing inorganic particles and organic polymers. The film formation method is performed by a one-step scraping coating and post-treatment in the aqueous phase to avoid the dense coating blocking the pores of the base separator.

Benefits of technology

It improves the electrochemical performance of aqueous zinc ion batteries, enhances the ionic conductivity of the separator, extends the cyclic stability of the battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118867575B_ABST
    Figure CN118867575B_ABST
Patent Text Reader

Abstract

The present invention provides an organic-inorganic hybrid battery separator, a preparation method thereof and an aqueous zinc ion battery, comprising boron-containing inorganic particles and an organic polymer; the boron-containing inorganic particles include one or more of boron nitride, boron carbide, aluminum diboride and titanium diboride; the mass ratio of the boron-containing inorganic particles to the organic polymer is 1: (3~15). The present invention forms a composite film of boron-containing inorganic particles and organic polymers, thereby avoiding the blockage of the pores of the base separator by the dense inorganic coating and also avoiding the shedding behavior of the surface coating during the battery cycle. At the same time, the boron-containing inorganic particles in the present invention provide good heat resistance and mechanical properties, optimize the structure of the polymer, regulate the zinc deposition behavior during the cycle, effectively improve the ionic conductivity of the separator, and enhance the electrochemical performance of the aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to an organic-inorganic hybrid battery separator, a preparation method thereof and an aqueous zinc ion battery. Background Art

[0002] With the rapid development of electrical equipment, the development of safe and environmentally friendly energy storage technology has become an important research direction for the next generation of energy storage systems. Aqueous zinc-ion batteries have non-toxic aqueous electrolytes, abundant and cheap zinc metal, and 819 mA hg -1 The high theoretical capacity and Zn / Zn 2+ Due to its low redox potential (-0.76 V vs. standard hydrogen electrode), it has become one of the most promising sustainable energy storage devices.

[0003] Among them, diaphragm materials play a key role in the safety and electrochemical stability of rechargeable batteries. The development of suitable diaphragms is crucial to the future development of the field of aqueous zinc-ion batteries. However, although commercial polyolefin diaphragms have good wettability in organic electrolytes and have been widely used in lithium-ion batteries, they are not hydrophilic and are not suitable for aqueous zinc-ion batteries. Glass fiber is one of the most commonly used diaphragm materials in aqueous zinc-ion batteries, but its high cost limits the large-scale application of aqueous zinc-ion batteries. Therefore, it is necessary to explore a new diaphragm preparation method that is cheap, convenient, and suitable for aqueous zinc-ion battery systems.

[0004] In order to further optimize battery performance, a variety of membrane functionalization methods have been developed, such as coating for surface functionalization, but the dense coating produced by simple surface functionalization will block the pores of the base membrane and affect ion transport. Summary of the invention

[0005] The purpose of the present invention is to provide an organic-inorganic hybrid battery separator, a preparation method thereof and an aqueous zinc ion battery. The separator of the present invention avoids the clogging of the pores of the base separator by the surface coating and improves the electrochemical performance of the aqueous zinc ion battery.

[0006] The present invention provides an organic-inorganic hybrid battery separator, comprising boron-containing inorganic particles and an organic polymer;

[0007] The boron-containing inorganic particles include one or more of boron nitride, boron carbide, aluminum diboride and titanium diboride;

[0008] The mass ratio of the boron-containing inorganic particles to the organic polymer is 1:(3-15).

[0009] Preferably, the particle size of the boron-containing inorganic particles is 1-2 μm.

[0010] Preferably, the organic polymer includes one or more of polyacrylonitrile, polymethyl methacrylate and polyvinylidene fluoride.

[0011] Preferably, the weight average molecular weight of the organic polymer is 50,000 to 1,000,000.

[0012] Preferably, the organic-inorganic hybrid aqueous zinc ion battery separator has a dense microporous structure with a porosity of 20-40%.

[0013] The present invention provides a method for preparing the organic-inorganic hybrid battery separator as described above, comprising the following steps:

[0014] A) mixing the boron-containing inorganic particles with a solvent to obtain a suspension;

[0015] B) mixing the suspension with an organic polymer and heating to obtain an organic-inorganic hybrid film-forming solution;

[0016] C) coating the organic-inorganic hybrid membrane-forming liquid to form a membrane to obtain a membrane intermediate;

[0017] D) replacing the separator intermediate in an aqueous phase to obtain an organic-inorganic hybrid battery separator.

[0018] Preferably, the solvent is a mixed solution of an organic solvent and water, and the organic solvent includes dimethyl sulfoxide and / or N, N-dimethylformamide;

[0019] The volume ratio of the organic solvent to water is (5-15):1.

[0020] Preferably, the mass ratio of the organic polymer to the solvent is 1:(8-10).

[0021] Preferably, the heating in step B) comprises two stages of heating, wherein the first stage of heating is at a temperature of 55-75° C. for 1-6 hours; and the second stage of heating is at a temperature of 75-95° C. for 1-6 hours.

[0022] The present invention provides an aqueous zinc ion battery, comprising the organic-inorganic hybrid battery separator described above.

[0023] The present invention provides an organic-inorganic hybrid battery separator, comprising boron-containing inorganic particles and organic polymers; the boron-containing inorganic particles include one or more of boron nitride, boron carbide, aluminum diboride and titanium diboride; the mass ratio of the boron-containing inorganic particles to the organic polymer is 1: (3-15). The present invention forms a composite film of the boron-containing inorganic particles and the organic polymer, thereby avoiding the blockage of the pores of the base separator by the dense inorganic coating and the possible shedding behavior of the surface coating during the battery cycle. At the same time, the boron-containing inorganic particles in the present invention provide better heat resistance and mechanical properties, optimize the structure of the polymer, regulate the zinc deposition behavior during the cycle, effectively improve the ionic conductivity of the separator, and enhance the electrochemical performance of the aqueous zinc ion battery.

[0024] Furthermore, the present invention utilizes the characteristics of polymers, adopts a one-step coating film-forming method, and performs post-processing and storage in the aqueous phase, which is universal in aqueous batteries. Compared with traditional electrospinning technology, the raw materials are cheap, the preparation cycle is short, the preparation process is simple, the required equipment is simple, the production process is safe, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0026] Figure 1 X-ray diffraction patterns of the diaphragms in Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention;

[0027] Figure 2 is a scanning electron microscope image of the surface of the diaphragm in Example 1 of the present invention;

[0028] Figure 3 is a scanning electron microscope image of a cross section of the diaphragm in Example 1 of the present invention;

[0029] Figure 4 C 1s spectra of X-ray photoelectron spectra of the diaphragms in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2;

[0030] Figure 5 The results are as follows: Examples 1 to 3 of the present invention, Comparative Examples 1 to 4 and commercial glass fiber separators in aqueous zinc ion batteries at 1 mA·cm -2 The current density and 1 mAh·cm -2 The charge and discharge cycle curve measured by the specific capacity;

[0031] Figure 6The present invention embodiment 1 and comparative example 1 are respectively in aqueous zinc ion batteries at 0.5~20 mA·cm -2 The current density and 1 mAh·cm -2 The rate performance curve measured by the specific capacity. DETAILED DESCRIPTION

[0032] The present invention provides an organic-inorganic hybrid battery separator, comprising boron-containing inorganic particles and an organic polymer;

[0033] The boron-containing inorganic particles include one or more of boron nitride, boron carbide, aluminum diboride and titanium diboride;

[0034] The mass ratio of the boron-containing inorganic particles to the organic polymer is 1:(3-15).

[0035] In the present invention, the particle size of the boron-containing inorganic particles is preferably 1-2 μm.

[0036] In the present invention, the organic polymer preferably includes one or more of polyacrylonitrile, polymethyl methacrylate and polyvinylidene fluoride, more preferably polyacrylonitrile; the weight average molecular weight of the organic polymer is preferably 50,000 to 1,000,000, more preferably 100,000 to 900,000, such as 50,000, 100,000, 150,000, 200,000, 250,000, 300,000, 350,000, 400,000, 450,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000, 850,000, 900,000, 950,000, 1,000,000, preferably with any of the above values ​​as the upper or lower limit of the range value. In the present invention, if the weight average molecular weight is too large, the polymer will be difficult to dissolve, and if it is too small, the mechanical properties of the polymer will be reduced.

[0037] In the present invention, the mass ratio of the boron-containing inorganic particles to the organic polymer is preferably 1:(3-15), more preferably 1:(5-12), such as 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, preferably a range value with any of the above values ​​as the upper or lower limit.

[0038] In the present invention, the organic-inorganic hybrid aqueous zinc ion battery separator has a dense microporous structure, and the pore size is preferably 15-25 nm; the porosity is preferably 20-40%, and more preferably 25-35%.

[0039] The present invention also provides a method for preparing the organic-inorganic hybrid battery separator as described above, comprising the following steps:

[0040] A) mixing the boron-containing inorganic particles with a solvent to obtain a suspension;

[0041] B) mixing the suspension with an organic polymer and heating to obtain an organic-inorganic hybrid film-forming solution;

[0042] C) coating the organic-inorganic hybrid membrane-forming liquid to form a membrane to obtain a membrane intermediate;

[0043] D) replacing the separator intermediate in an aqueous phase to obtain an organic-inorganic hybrid battery separator.

[0044] In the present invention, the type and amount of the boron-containing inorganic particles are consistent with the boron-containing inorganic particles described above, and the present invention will not be repeated here.

[0045] In the present invention, the solvent is preferably a mixture of an organic solvent and water, and the organic solvent preferably includes dimethyl sulfoxide and / or N, N-dimethylformamide; the volume ratio of the organic solvent to water is preferably (5-15):1, more preferably (8-12):1, such as 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, preferably a range value with any of the above values ​​as the upper or lower limit.

[0046] In the present invention, the mass ratio of the organic polymer to the solvent is preferably 1:(8-10), more preferably 1:9.

[0047] After obtaining the suspension, the present invention mixes the suspension with an organic polymer and heats the mixture in a water bath to obtain an organic-inorganic hybrid film-forming liquid.

[0048] In the present invention, the type and amount of the organic polymer are consistent with the type and amount of the organic polymer described above, and the present invention will not be repeated here.

[0049] In the present invention, the heating is preferably divided into two stages, the purpose of the first stage heating process is to swell the organic polymer, and the purpose of the second stage heating is to further dissolve the organic polymer. The insulation temperature of the first stage heating is preferably 55-75°C, more preferably 60-70°C, such as 55°C, 60°C, 65°C, 70°C, 75°C, preferably a range value with any of the above values ​​as the upper or lower limit; the insulation time of the first stage heating is preferably 1-6 hours, more preferably 2-5 hours, and most preferably 3-4 hours; the insulation temperature of the second stage heating is preferably 75-95°C, more preferably 80-90°C, such as 75°C, 80°C, 85°C, 90°C, 95°C, preferably a range value with any of the above values ​​as the upper or lower limit; the insulation time of the second stage heating is preferably 1-6 hours, more preferably 2-5 hours, and most preferably 3-4 hours.

[0050] After obtaining the organic-inorganic hybrid film-forming liquid, the present invention adopts a one-step scraping film-forming method to scrape a certain thickness of the organic-inorganic hybrid film-forming liquid on a substrate, and after cooling the film, remove it from the substrate to obtain a diaphragm intermediate.

[0051] In the present invention, the coating thickness is preferably 500-1000 μm, more preferably 600-800 μm, such as 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, preferably a range value with any of the above values ​​as the upper or lower limit.

[0052] In the present invention, the cooling temperature is preferably room temperature, such as 20-30°C, more preferably 25°C.

[0053] After obtaining the diaphragm intermediate, the present invention washes the diaphragm intermediate with deionized water, immerses it in water for replacement, removes the organic solvent, and obtains an organic-inorganic hybrid battery diaphragm. The obtained organic-inorganic hybrid battery diaphragm can be immersed in deionized water for storage.

[0054] The present invention also provides an aqueous zinc ion battery, which comprises the organic-inorganic hybrid battery separator described above.

[0055] In the present invention, the positive electrode, negative electrode and electrolyte of the aqueous zinc ion battery can all adopt the positive electrode, negative electrode and electrolyte of aqueous zinc ion batteries commonly used in the art, and the present invention will not be repeated here.

[0056] The present invention provides an organic-inorganic hybrid battery separator, comprising boron-containing inorganic particles and organic polymers; the boron-containing inorganic particles include one or more of boron nitride, boron carbide, aluminum diboride and titanium diboride; the mass ratio of the boron-containing inorganic particles to the organic polymer is 1: (3-15). The present invention forms a composite film of the boron-containing inorganic particles and the organic polymer, thereby avoiding the blockage of the pores of the base separator by the dense inorganic coating and the possible shedding behavior of the surface coating during the battery cycle. At the same time, the boron-containing inorganic particles in the present invention provide better heat resistance and mechanical properties, optimize the structure of the polymer, regulate the zinc deposition behavior during the cycle, effectively improve the ionic conductivity of the separator, and enhance the electrochemical performance of the aqueous zinc ion battery.

[0057] Furthermore, the present invention utilizes the characteristics of polymers, adopts a one-step coating film-forming method, and performs post-processing and storage in the aqueous phase, which is universal in aqueous batteries. Compared with traditional electrospinning technology, the raw materials are cheap, the preparation cycle is short, the preparation process is simple, the required equipment is simple, the production process is safe, and it is suitable for large-scale production.

[0058] In order to further illustrate the present invention, an organic-inorganic hybrid battery separator, a preparation method thereof and an aqueous zinc ion battery provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0059] Example 1

[0060] 1) Add 36.25 mL of dimethyl sulfoxide to 5 mL of water and stir for 35 minutes to mix well;

[0061] 2) Weigh 1 g of boron nitride, add it to the above solution, and stir for 35 minutes to make it evenly dispersed;

[0062] 3) Weigh 5 g of polyacrylonitrile (weight average molecular weight of 800,000 to 1,000,000), add it to the above mixed solution, and stir for 35 minutes to make it evenly dispersed;

[0063] 4) The above solution was heated in a water bath with stirring, maintained at 65°C for 3 h, and then maintained at 85°C for 3 h;

[0064] 5) Using a scraping film preparation device, control the scraping film thickness to 750 μm, and scrape the above solution onto a stainless steel plate;

[0065] 6) After the film is cooled and formed at 25 °C, it is placed in an aqueous phase to replace and remove the organic solvent to obtain a polyacrylonitrile-boron nitride hybrid membrane.

[0066] Figure 1 The X-ray diffraction patterns of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 are schematically shown.

[0067] like Figure 1 As shown, in Figure 1 In the X-ray diffraction test results shown, the polyacrylonitrile-boron nitride hybrid membrane has diffraction peaks of both inorganic boron nitride particles and organic polymer polyacrylonitrile, which indicates the successful synthesis of the organic-inorganic hybrid membrane.

[0068] Figure 2 The surface scanning electron microscope image of the diaphragm in Example 1 of the present invention is schematically shown.

[0069] Figure 3 The cross-sectional scanning electron microscope image of the diaphragm in Example 1 of the present invention is schematically shown.

[0070] like Figure 2 , Figure 3 As shown in the figure, scanning electron microscopy shows that the polyacrylonitrile-boron nitride hybrid separator has a dense microporous structure. This structure is conducive to improving the electrolyte wettability and ion diffusion of the separator, thereby improving the electrochemical performance of aqueous zinc-ion batteries.

[0071] Example 2

[0072] In step 2), boron carbide is used as inorganic particles, and the rest is the same as in Example 1 to obtain a polyacrylonitrile-boron carbide hybrid diaphragm.

[0073] Figure 1 The X-ray diffraction patterns of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 are schematically shown.

[0074] like Figure 1 As shown, in Figure 1 In the X-ray diffraction test results shown, the polyacrylonitrile-boron carbide hybrid membrane has diffraction peaks of both inorganic boron carbide particles and organic polymer polyacrylonitrile, which indicates the successful synthesis of the organic-inorganic hybrid membrane.

[0075] Example 3

[0076] In step 2), aluminum diboride is used as inorganic particles, and the rest is the same as in Example 1 to obtain a polyacrylonitrile-aluminum diboride hybrid diaphragm.

[0077] Figure 1 The X-ray diffraction patterns of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 are schematically shown.

[0078] like Figure 1 As shown, in Figure 1 In the X-ray diffraction test results shown, the polyacrylonitrile-aluminum diboride hybrid membrane has diffraction peaks of both inorganic aluminum diboride particles and organic polymer polyacrylonitrile, which indicates the successful synthesis of the organic-inorganic hybrid membrane.

[0079] Example 4

[0080] In step 1), N,N-dimethylformamide is used as the organic solvent, and the rest is the same as in Example 1.

[0081] Example 5

[0082] In step 2), 0.5 g of boron nitride is used as inorganic particles, and the rest is the same as in Example 1.

[0083] Example 6

[0084] In step 5), the thickness of the scraped film is controlled to be 500 μm, and the rest is the same as in Example 1.

[0085] Example 7

[0086] In step 5), the thickness of the scraped film is controlled to be 1000 μm, and the rest is the same as in Example 1.

[0087] Comparative Example 1

[0088] In step 2), no inorganic particles are added, and the rest is the same as in Example 1 to obtain a polyacrylonitrile separator.

[0089] Figure 1 The X-ray diffraction patterns of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 are schematically shown.

[0090] Comparative Example 2

[0091] In step 2), aluminum nitride is used as the inorganic particle, and the rest is the same as in Example 1 to obtain a polyacrylonitrile-aluminum nitride hybrid diaphragm.

[0092] Figure 1 The X-ray diffraction patterns of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 are schematically shown.

[0093] like Figure 1 As shown, in Figure 1 In the X-ray diffraction test results shown, the polyacrylonitrile-aluminum nitride hybrid membrane has diffraction peaks of both inorganic aluminum nitride particles and organic polymer polyacrylonitrile, which indicates the successful synthesis of the organic-inorganic hybrid membrane.

[0094] Figure 4 The C 1s spectra of the X-ray photoelectron spectra of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 are schematically shown.

[0095] like Figure 1 As shown, in Figure 4 In the X-ray photoelectron spectroscopy detection results shown, compared with the polyacrylonitrile membrane and the polyacrylonitrile-aluminum nitride hybrid membrane, the content of C≡N bonds in the polyacrylonitrile membrane with added boron-containing inorganic particles is significantly reduced, indicating that the boron element can adjust the functional group structure of polyacrylonitrile.

[0096] Comparative Example 3

[0097] In step 2), aluminum oxide is used as inorganic particles, and the rest is the same as in Example 1 to obtain a polyacrylonitrile-aluminum oxide hybrid diaphragm.

[0098] Comparative Example 4

[0099] In step 2), silicon dioxide is used as inorganic particles, and the rest is the same as in Example 1 to obtain a polyacrylonitrile-silicon dioxide hybrid diaphragm.

[0100] The electrochemical performance of Examples 1 to 3, Comparative Examples 1 to 4 and commercial glass fiber separators as aqueous zinc ion battery separators was evaluated. The specific steps and results are as follows:

[0101] All electrochemical data tests were carried out in an aqueous zinc-ion symmetric cell.

[0102] The prepared modified polyacrylonitrile-based film was cut into discs with a radius of 10 mm and used as a separator. A zinc sheet with a thickness of 100 μm and a radius of 6 mm was used as an electrode and a 2 M zinc sulfate solution was used as an electrolyte to assemble a button-type zinc ion symmetrical battery. The electrochemical performance of the aqueous zinc ion battery was tested using the Blue Battery Test System.

[0103] A stainless steel mesh with a radius of 6 mm was used as an electrode and a 2 M zinc sulfate solution was used as an electrolyte to assemble a button-type zinc ion symmetrical battery. The electrochemical impedance spectroscopy test was performed using a blue battery test system. The ionic conductivity of the diaphragm prepared in Example 1 was calculated to be 18.49 mS·cm -1 The ionic conductivity of the membrane prepared in Comparative Example 1 is 6.03 mS·cm -1 .

[0104] Figure 5 The schematic diagram shows the performance of Examples 1-3, Comparative Examples 1-4 and commercial glass fiber separators in aqueous zinc ion batteries at 1 mA cm -2 The current density and 1 mAh cm -2 The charge and discharge cycle curve measured by the specific capacity.

[0105] like Figure 5 As shown, the polyacrylonitrile-boron-containing inorganic particle hybrid membranes prepared by Examples 1 to 3 all exhibit good long-cycle stability, among which the polyacrylonitrile-boron nitride hybrid membrane prepared in Example 1 exhibits a long-cycle stability of 1000 hours in an aqueous zinc ion battery, which is far superior to commercial glass fiber membranes.

[0106] Figure 6 The schematic diagram shows that Example 1 and Comparative Example 1 are respectively used in aqueous zinc ion batteries at 0.5-20 mA cm -2 The current density and 1 mAh cm -2 The rate performance curve measured by the specific capacity.

[0107] like Figure 6 As shown, at 1 mAh cm -2 Under the conditions of 0.5 mA cm -2 , 1 mA cm -2 , 3 mA cm -2 , 5mA cm -2 , 10 mA cm -2 , 20 mA cm -2The current density test of the aqueous zinc ion battery assembled by Example 1 and Comparative Example 1 shows good stability when the polyacrylonitrile-boron nitride hybrid diaphragm prepared by Example 1 is cycled at different current densities. At the same time, the polyacrylonitrile-boron nitride hybrid diaphragm has the characteristics of high current resistance and can be used at 20 mA cm -2 Compared with the commercial glass fiber separator and comparative example 1, the rate capability and high current resistance performance of the organic-inorganic hybrid separator are greatly improved.

[0108] From the above examples 1 to 3, comparative examples 1 to 4 and commercial glass fiber separators, it can be seen that the organic-inorganic hybrid aqueous zinc ion battery separator prepared by the present invention has a dense microporous structure, wherein the boron-containing inorganic particles can reduce the content of C≡N bonds, adjust the functional group structure of polyacrylonitrile, increase the affinity with zinc ions, and increase the ionic conductivity of the separator by 3 times. Therefore, the aqueous zinc ion battery using the organic-inorganic hybrid separator has the characteristics of long cycle stability and high current resistance, and is superior to the commercial glass fiber separator.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an organic-inorganic hybrid battery separator in an aqueous zinc ion battery, comprising the following steps: A) mixing the boron-containing inorganic particles with a solvent to obtain a suspension; The boron-containing inorganic particles include one or more of boron nitride, boron carbide, aluminum diboride and titanium diboride; the solvent is a mixed solution of an organic solvent and water, and the organic solvent includes dimethyl sulfoxide and / or N, N-dimethylformamide; the volume ratio of the organic solvent to water is (5-15):1; B) mixing the suspension with a cyano-containing organic polymer, and heating to obtain an organic-inorganic hybrid film-forming solution; the cyano-containing organic polymer is polyacrylonitrile; and the mass ratio of the cyano-containing organic polymer to the solvent is 1:(8-10); The heating in step B) specifically includes two stages of heating, the first stage of heating is at a temperature of 55-75°C for 1-6 hours; the second stage of heating is at a temperature of 75-95°C for 1-6 hours; C) applying a blade coating on the organic-inorganic hybrid film-forming liquid to form a film to obtain a diaphragm intermediate; D) replacing the membrane intermediate in an aqueous phase to obtain an organic-inorganic hybrid battery membrane, and the obtained organic-inorganic hybrid battery membrane is immersed in deionized water for storage.

2. An aqueous zinc ion battery, characterized in that: It comprises an organic-inorganic hybrid battery separator, which is prepared according to the preparation method of claim 1, and comprises boron-containing inorganic particles and cyanide-containing organic polymers.

3. The aqueous zinc ion battery according to claim 2, characterized in that: The particle size of the boron-containing inorganic particles is 1-2 μm.

4. The aqueous zinc ion battery according to claim 2, characterized in that: The weight average molecular weight of the cyano group-containing organic polymer is 50,000 to 1,000,000.

5. The aqueous zinc ion battery according to claim 2, characterized in that: The organic-inorganic hybrid battery separator has a dense microporous structure with a porosity of 20-40%.

Citation Information

Patent Citations

  • A separator for a lithium ion battery

    CN102810656A

  • Composite diaphragm with high conductivity material layer and preparation method thereof

    CN109860477A

  • C 3n 4 modified organic film preparation method and application

    WO2021093832A1